Inheriting Gandhi: influences, activisms - Kumar, Satishchandra; Kanchana Mahadevan; Bhoot, Meher; Kharat, Rajesh S.; Bilgrami, Akeel (Speaking Tiger in association with University of Mumbai, 2022)
Published earlier in Sambhashan online journal of University of Mumbai